The Influence of Work Motivation on the Performance of Security Employees at Light Rail Transit PT. Kereta Api Indonesia Division III, Palembang City, South Sumatra - Rahmawati, Rahmawati; Habena, A. Ridhuan; Aryanisila, Aryanisila; Supardi , Supardi (Journal of Social and Policy Issues, 2025)
This research was conducted with the aim of testing and analyzing the influence of work motivation on the performance of security employees at the Light Rail Transit (LRT) in South Sumatra. The variables in this research are work motivation and employee performance. The sample used was 100 South Sumatra Palembang LRT security employees with a sampling technique using cluster sampling. The primary and secondary data used in this research are primary and secondary data. The research method used was quantitative, and the data collection method was questionnaires and documentation. The test equipment used is SPSS version 26, and Amos version 20, with the data analysis techniques used are simple linear regression analysis techniques, t test, and coefficient of determination. The results of this research work show that work motivation influences the performance of South Sumatra LRT security employees. From the results of the research explained in the previous chapter, it can be concluded that the Work Motivation Variable (X1) influences the performance of South Sumatra LRT Security Employees. This is proven by the research results with a calculated t value of 26.339 > t table 1.660 and a significance value of 0.000 < 0.05 with an influence level of 95%.